Some aspects of civil and arbitrary proceeding in EU law practice - Tretyakova, Tatyana (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the consideration of certain aspects of the civil and arbitration process in the European Union. The author analyzed the concept of European civil and arbitration law, highlighted the significant difference between the two processes in the EU, identified the leading principles for the implementation of arbitration. The analysis of the advantages of the European Union arbitration institutions is carried out, on the basis of which the advantages of the arbitration procedure are identified, at the same time, the shortcomings of the European arbitration are realistically considered.The relevance of the research topic is due to the ongoing changes in the system of pan-European and national law, which relate to civil and arbitration legislation. Possession of information on current changes and stages of development of European arbitration makes it possible to monitor the state of the Russian arbitration system in order to highlight the main shortcomings and further correct them.Objective: to highlight the difference and similarity of certain aspects of the civil and arbitration processes.Research methods: analysis of the scientific literature on the problem, deduction, induction, comparison, analogy.